Three fudges and a baby - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2024)
When her very pregnant best friend Jenn's doula is accused of murder, Ally agrees to prove the doula's innocence and races against time to solve the case before Jenn's special delivery arrives.